Św . Jan Klimak, O wyrzeczeniu się świata (Scala paradisi. Gradus Primus. De abdicatione ritae saecularis. Patrologia graeca 88, 632-644) - Jasiewicz, Arkadiusz (Śląskie Studia Historyczno-Teologiczne, 2011)
There is not too much known about the life of St. John Climacus. According to most, he was born approximately around the time 579 AD and died around 649 AD . He was sixteen years old when he first came to Sinai where there already existed a well established monastic life. After forty years as a hermit, St. John, against his will, was elected abbot at the central monastery of Sinai. It is not known how long he continued in his office as abbot but it was during the last period of his life that he composed The Ladder of Divine Ascent, at the request of another John, the superior of a nearby monastery at Raithu. The Ladder was written by a solitary for cenobites. Although written primarily for monastics, St. John affirms God’s universal love for the monastic and non-monastic alike, also pointing out that celibacy is in no way a requirement for purity. The ladder has thirty steps, each symbolizing a year in the hidden life of Christ before his baptism. It begins with the basic notion of turning or conversion, continuing with a detailed analysis of the virtues and vices, and then ending with union with God. This translation describe the first level of spiritual life: on renunciation of the world.